Nitrogen-doped porous hard carbon for negative electrode of sodium-ion battery as well as preparation method and application of nitrogen-doped porous hard carbon
By using nitrogen-doped porous hard carbon as the negative electrode material of sodium ion battery, the problems of poor microstructure, weak conductivity and complex and high cost in the prior art negative electrode material are solved, and the specific capacity of the battery and the active sodium storage position are improved. The effect of the dot.
Patent Information
- Application Number
- CN202411509226.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-10-28
AI Technical Summary
The existing negative electrode materials of sodium ion batteries have problems such as microstructure smooth sheet structure, weak conductivity, poor sodium storage capacity, cumbersome process flow and high cost.
Nitrogen-doped porous hard carbon is used as the negative electrode material of sodium ion battery. Through the mixing, cross-linking pre-carbonization and pyrolysis reaction of carbon nitride and starch, a hard carbon material with rich pore structure and nitrogen doped elements is formed.
The specific capacity and sodium storage active sites of sodium ion batteries are improved, the process flow is simplified, the production cost is reduced, and the problem of starch pyrolysis expansion, melt foaming is solved.
Smart Images

Figure CN119430127A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to nitrogen-doped porous hard carbon for a negative electrode of a sodium ion battery, and a preparation method and application thereof. Background Art
[0002] With the development of global society, the use of fossil fuels, mainly coal, oil and natural gas, is increasing, and the pollution and damage to the environment are becoming more and more serious, making the demand for renewable clean energy become greater and greater. However, renewable clean energy such as solar energy, hydropower, and wind energy has regionality, climate and randomness, resulting in unstable power generation and uncertain power generation time. Therefore, the development of energy storage technology is urgent. In recent years, with the development of new energy, the demand for energy storage batteries has increased. In particular, lithium-ion batteries have attracted widespread attention due to their high energy density and long cycle life. Faced with the severe situation of lithium ore resource shortage, uneven distribution and high cost, sodium-ion batteries have become a new research hotspot in large-scale energy storage technology due to their low cost and abundant natural resources.
[0003] Thermodynamically, the binding energy between sodium ions and carbon is low, and they cannot form LiC like lithium ions and graphite. 6 Intercalation compounds form NaC 6 structure. As a result, sodium ions cannot be well embedded in the graphite layer. Therefore, industry insiders gave up the application of graphite to the negative electrode of sodium ion batteries and turned to study the feasibility of using hard carbon in the negative electrode of sodium ion batteries. Hard carbon can be prepared through a series of chemical changes using resin, coal tar, biomass, etc. as precursors. From the perspective of market economy, the stable batch supply of precursors and the low cost of production process are the core considerations for the maturity of hard carbon technology. However, the existing hard carbon materials have the following defects: although resin-based hard carbon has good performance, the production process is cumbersome and complicated, and the raw materials are expensive; although coal tar has a high hydrogen content, high-temperature pyrolysis often only produces low-performance soft carbon; although biomass has a wide source, the element content is unstable and is affected by regional, climate, season and other issues. For this reason, finding a biomass precursor with a wide and stable source and low cost to prepare and synthesize high-performance hard carbon is still a difficulty that needs to be overcome.
[0004] In the prior art, a Chinese patent application with application number CN118538913A discloses that doping boron into starch-derived hard carbon can effectively improve the ion diffusion rate, while taking into account high first-cycle coulomb efficiency and capacity. A patent application with application number CN118439585A discloses the use of sodium carbonate as a template agent to make starch-derived hard carbon have a nanoporous structure, and can effectively inhibit the adverse reaction of starch melting, foaming and expansion during starch pyrolysis. However, the above-mentioned prior art has the following disadvantages: (1) Although starch is a renewable precursor for preparing hard carbon, the microstructure of hard carbon obtained directly by pyrolyzing starch is a smooth lamellar structure, which is attributed to the fact that starch will melt, expand and foam during high-temperature pyrolysis. When this melt-expanded and foamed starch-derived hard carbon was used as a sodium ion battery negative electrode for cycle testing, it was found that the specific capacity was very low and it was not suitable for use as a sodium ion battery negative electrode material. (2) The elements contained in starch are carbon, hydrogen and oxygen, which makes the hard carbon obtained by pyrolyzing starch weak in conductivity and charge transfer ability, which in turn leads to very low sodium storage capacity and almost no sodium storage performance. (3) The two modification methods of hard carbon - pore creation and doping require two independent steps to be completed one after another, and the template and dopant used are often not the same chemical. This leads to the defects of cumbersome and complicated process flow and high production cost. Summary of the invention
[0005] In order to overcome the shortcomings of the prior art, the first purpose of the present invention is to provide a method for preparing nitrogen-doped porous hard carbon for sodium ion battery negative electrode. The preparation method has a simple process and low production cost, solves the problem of pyrolysis, expansion, melting and foaming of pure starch, and is suitable for use as a negative electrode material for sodium ion batteries to improve the specific capacity of the battery.
[0006] In order to overcome the shortcomings of the prior art, the second object of the present invention is to provide a nitrogen-doped porous hard carbon for a sodium ion battery negative electrode. The nitrogen-doped porous hard carbon for a sodium ion battery negative electrode is suitable for use as a sodium ion battery negative electrode material, can increase sodium storage active sites, and improve the specific capacity of the battery.
[0007] The third object of the present invention is to provide an application of the nitrogen-doped porous hard carbon in the negative electrode material of a sodium ion battery.
[0008] The fourth object of the present invention is to provide an application of the nitrogen-doped porous hard carbon in a sodium ion battery.
[0009] In order to achieve the first object of the above invention, the technical solution adopted by the present invention is as follows:
[0010] The present invention provides a method for preparing nitrogen-doped porous hard carbon for a negative electrode of a sodium ion battery, comprising the following steps:
[0011] S1. Mixing carbon nitride and starch: placing carbon nitride, starch and anhydrous ethanol in a container and then mixing them to obtain a mixture;
[0012] S2, solid-liquid separation and drying: separating the mixture obtained in step S1 into anhydrous ethanol and mixed powder, and drying the mixed powder;
[0013] S3, cross-linking pre-carbonization: under the protection of inert gas, heating the mixed powder dried in step S2 for cross-linking pre-carbonization;
[0014] S4, pyrolysis reaction: After the cross-linking pre-carbonization in step S3 is completed, the temperature is continued to be raised to carry out pyrolysis reaction, so as to obtain the nitrogen-doped porous hard carbon for the negative electrode of the sodium ion battery.
[0015] Furthermore, in the step S1, the carbon nitride is prepared by subjecting urea to a thermal decomposition reaction under the protection of an inert gas to obtain the carbon nitride.
[0016] Furthermore, the preparation method of the carbon nitride is: placing urea in a porcelain boat, then putting it into a tubular furnace, heating it from room temperature to 500°C-600°C at a heating rate of 3°C / min-7°C / min under the protection of nitrogen, and thermally decomposing it for 2h-4h, and then naturally cooling it to room temperature to obtain carbon nitride powder; the flow rate of the nitrogen is 15mL / min-25mL / min.
[0017] Further, in step S1, the mass ratio of the carbon nitride to the starch is 1:(1-5); the mass volume ratio of the total mass of the carbon nitride and the starch to the anhydrous ethanol is 3g:(100mL-300mL); and / or
[0018] In the step S1, the mixing is to place the container containing carbon nitride, starch and anhydrous ethanol into an ultrasonic instrument for ultrasonic dispersion for 20 minutes to 40 minutes, and then stir with a magnetic stirrer for 5 hours to 7 hours.
[0019] Among them, the preparation method of nitrogen-doped porous hard carbon for the negative electrode of a sodium ion battery of the present invention adopts anhydrous ethanol as the liquid medium for mixing carbon nitride and starch, and then can adopt ultrasonic resonance of an ultrasonic instrument and stirring treatment of a magnetic stirrer to fully disperse starch particles and carbon nitride particles, thereby making the carbon nitride and starch fully mixed, which has the advantage of good mixing effect, and is beneficial to the subsequent cross-linking pre-carbonization and pyrolysis reaction. The pore structure formed by the pore-forming effect of carbon nitride on the hard carbon is more uniform, and the nitrogen element enters the hard carbon to form sodium storage active sites more uniformly.
[0020] Furthermore, in step S2, the mixture obtained in step S1 is filtered to separate anhydrous ethanol and mixed powder, and the mixed powder is placed in a forced air drying oven at 50° C.-70° C. and dried for 10 h-14 h.
[0021] Furthermore, in step S3, the dried mixed powder is placed in a porcelain boat and sent into a tubular furnace. Under the protection of nitrogen, the temperature is increased to 180°C-220°C at a heating rate of 3°C / min-7°C / min and kept for 3h-5h for cross-linking pre-carbonization.
[0022] Furthermore, in step S4, after the cross-linking pre-carbonization of step S3 is completed, the temperature is continued to be raised to 800°C-1600°C at a heating rate of 3°C / min-7°C / min for pyrolysis reaction for 1h-3h to obtain the nitrogen-doped porous hard carbon for the negative electrode of the sodium ion battery.
[0023] In order to achieve the second purpose of the above invention, the technical solution adopted by the present invention is as follows:
[0024] The present invention provides a nitrogen-doped porous hard carbon for a negative electrode of a sodium ion battery, which is prepared by the above-mentioned method for preparing nitrogen-doped porous hard carbon for a negative electrode of a sodium ion battery.
[0025] In order to achieve the third purpose of the above invention, the technical solution adopted by the present invention is as follows:
[0026] The present invention provides a sodium ion battery negative electrode, which is prepared from the nitrogen-doped porous hard carbon described above.
[0027] In order to achieve the fourth object of the above invention, the technical solution adopted by the present invention is as follows:
[0028] The present invention provides a sodium ion battery, which is prepared by using the nitrogen-doped porous hard carbon as a negative electrode material.
[0029] Among them, the role of the template is to change the microscopic morphology of the target product (hard carbon) in a directional manner. Different templates have different effects on the changes in the microscopic morphology of the target product (hard carbon). The function of some templates is to make pores in the hard carbon to form a pore structure, and the function of some templates is to transform the hard carbon into a specific shape. The template in the prior art does not have the sodium storage property, so it does not contribute to the specific capacity, and the specific capacity is only provided by the hard carbon. The hard carbon with residual template is assembled into a button battery. Since the template occupies part of the mass of the negative electrode and does not have the sodium storage property, the specific capacity of the button battery will be reduced. Therefore, the prior art needs to remove the template. If the template is not removed, as the hard carbon is assembled into the interior of the button battery, it will contact the electrolyte inside the battery. The template may produce side reactions with part of the electrolyte and consume the electrolyte. The impurities generated by the side reactions prevent the remaining electrolyte from contacting the negative electrode, resulting in less electrolyte participating in the charge and discharge cycle between the positive and negative electrodes, thereby reducing the specific capacity.
[0030] The present invention discloses a method for preparing nitrogen-doped porous hard carbon for the negative electrode of a sodium ion battery. In the process of keeping the mixed powder of carbon nitride and starch at 180°C-220°C, the carbon nitride is continuously cross-linked to wrap the starch. The carbon nitride is cross-linked with the starch particles to wrap the starch particles one by one, thereby blocking the contact and melting between the starch particles. Then, when the temperature is further raised to the pyrolysis temperature, the starch is carbonized into hard carbon, the carbon nitride is gasified and decomposed, and holes of different sizes are left in situ (self-sacrifice); the carbon nitride that is not gasified and decomposed is cross-linked with the hard carbon in situ to become part of the hard carbon bulk phase. The co-pyrolysis of the mixture of carbon nitride and starch changes the microscopic morphology of the starch hard carbon, so that the hard carbon with a smooth lamellar structure originally in the microscopic morphology is changed into a hard carbon with a rich pore structure, which greatly increases the specific surface area and greatly enriches the storage sites of sodium ions; and a certain amount of nitrogen is doped into the bulk of the hard carbon, further increasing the storage active sites of sodium ions, so it has the advantages of high first-cycle coulomb efficiency and large specific capacity.
[0031] The present invention discloses a method for preparing nitrogen-doped porous hard carbon for a negative electrode of a sodium ion battery. Carbon nitride is mixed with starch and pyrolyzed together. By utilizing the characteristics of carbon nitride that can be integrated into the bulk phase of starch-derived hard carbon and the characteristics of self-sacrificial pore formation, a portion of the carbon nitride is integrated into the bulk phase of hard carbon as a dopant, and another portion of the carbon nitride is decomposed, gasified and volatilized at high temperature, leaving pores of different sizes in situ. In addition, nitrogen element is doped without the need for additional process steps to remove excess carbon nitride, because a portion of the carbon nitride that is not integrated into the bulk phase of starch-derived hard carbon can be decomposed, gasified and volatilized at high temperature. In addition, pore formation for starch-derived hard carbon does not require an additional process step to remove the template, and the residual carbon nitride is integrated into the bulk phase of starch-derived hard carbon. In addition, the co-pyrolysis of carbon nitride and starch can effectively suppress the problem of starch melting, foaming and expansion during high-temperature pyrolysis. Therefore, the present invention has a simple process flow, low cost, and has the dual functions of doping and pore formation for hard carbon.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] (1) The present invention provides a method for preparing nitrogen-doped porous hard carbon for a negative electrode of a sodium ion battery. The method uses carbon nitride as a self-sacrificial template and performs a co-pyrolysis reaction with starch after cross-linking and pre-carbonization. The carbon nitride acts as both a self-sacrificial template and a dopant, and has the dual functions of pore formation and nitrogen doping. On the one hand, the carbon nitride can form pores in the hard carbon and make the hard carbon have a rich pore structure. On the other hand, the carbon nitride can dope nitrogen into the bulk of the hard carbon. The combined action of the two greatly increases the sodium storage active sites, which can store a large amount of sodium ions, thereby improving the specific capacity of the sodium ion battery. In addition, the co-pyrolysis of carbon nitride and starch solves the problem of pure starch pyrolysis expansion, melting and foaming.
[0034] (2) The present invention provides a method for preparing nitrogen-doped porous hard carbon for a negative electrode of a sodium ion battery. After carbon nitride and starch are mixed, separated and dried, cross-linked pre-carbonization and pyrolysis reaction are carried out to obtain nitrogen-doped porous hard carbon. The preparation method has the characteristics of simple process, simple and convenient operation, low production cost, and applicability to large-scale production.
[0035] (3) The nitrogen-doped porous hard carbon for the negative electrode of a sodium ion battery of the present invention has a rich pore structure and nitrogen is doped in the hard carbon, which can increase the sodium storage active sites and is suitable for use as a negative electrode material for sodium ion batteries to improve the specific capacity of the battery.
[0036] (4) The negative electrode of a sodium ion battery of the present invention is made of the nitrogen-doped porous hard carbon of the present invention, and therefore has abundant sodium storage active sites, can store a large amount of sodium ions, and thus can improve the specific capacity of the sodium ion battery.
[0037] (5) The application of the nitrogen-doped porous hard carbon of the present invention in sodium ion batteries, the prepared sodium ion batteries have abundant sodium storage active sites, can store a large amount of sodium ions, and thus can improve the specific capacity of the sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0039] Figure 1 This is a SEM image of nitrogen-doped porous hard carbon for a negative electrode of a sodium ion battery prepared in Example 1 of the present invention.
[0040] Figure 2 This is a SEM image of nitrogen-doped porous hard carbon for a negative electrode of a sodium ion battery prepared in Example 2 of the present invention.
[0041] Figure 3 This is a SEM image of nitrogen-doped porous hard carbon for a negative electrode of a sodium ion battery prepared in Example 3 of the present invention.
[0042] Figure 4 This is a SEM image of nitrogen-doped porous hard carbon for a negative electrode of a sodium ion battery prepared in Example 4 of the present invention.
[0043] Figure 5 This is a SEM image of nitrogen-doped porous hard carbon for a negative electrode of a sodium ion battery prepared in Example 5 of the present invention.
[0044] Figure 6 This is a SEM image of a hard carbon prepared in Comparative Example 1 of the present invention.
[0045] Figure 7 This is an XPS diffraction nitrogen element detection diagram of nitrogen-doped porous hard carbon for a negative electrode of a sodium ion battery prepared in Example 1 of the present invention.
[0046] Figure 8 This is a physical picture of a sodium ion battery according to Example 9 of the present invention.
[0047] Fig. 9 This is a constant current charge and discharge curve diagram of a sodium ion battery according to Example 6 of the present invention.
[0048] Fig.10 This is a constant current charge and discharge curve diagram of a sodium ion battery according to Example 7 of the present invention.
[0049] Fig.11 This is a constant current charge and discharge curve diagram of a sodium ion battery according to Example 8 of the present invention.
[0050] Fig.12 This is a constant current charge and discharge curve diagram of a sodium ion battery according to Example 9 of the present invention.
[0051] Fig.13 This is a constant current charge and discharge curve diagram of a sodium ion battery according to Example 10 of the present invention.
[0052] Fig.14 It is a constant current charge and discharge curve diagram of a sodium ion battery in comparative example 2 of the present invention.
[0053] Fig.15 This is a 300-cycle performance diagram of a sodium ion battery according to Example 6 of the present invention.
[0054] Fig.16 This is a 300-cycle performance diagram of a sodium ion battery according to Example 7 of the present invention.
[0055] Fig.17 This is a 300-cycle performance diagram of a sodium ion battery according to Example 8 of the present invention.
[0056] Fig.18 This is a 300-cycle performance diagram of a sodium ion battery according to Example 9 of the present invention.
[0057] Fig.19 This is a 300-cycle performance diagram of a sodium ion battery according to Example 10 of the present invention.
[0058] Fig. 20 This is a 300-cycle performance diagram of a sodium ion battery in Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0059] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0060] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. In the present invention, the singular forms "a", "said" and "the" used in the embodiments and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0061] In an embodiment of the present invention, a method for preparing nitrogen-doped porous hard carbon for a negative electrode of a sodium ion battery comprises the following steps:
[0062] S1. Mixing carbon nitride and starch: placing carbon nitride, starch and anhydrous ethanol in a container and then mixing them to obtain a mixture;
[0063] S2, solid-liquid separation and drying: separating the mixture obtained in step S1 into anhydrous ethanol and mixed powder, and drying the mixed powder;
[0064] S3, cross-linking pre-carbonization: under the protection of inert gas, heating the mixed powder dried in step S2 for cross-linking pre-carbonization;
[0065] S4, pyrolysis reaction: After the cross-linking pre-carbonization in step S3 is completed, the temperature is continued to be raised to carry out pyrolysis reaction, so as to obtain the nitrogen-doped porous hard carbon for the negative electrode of the sodium ion battery.
[0066] In some embodiments, in step S1, the method for preparing the carbon nitride is: under the protection of an inert gas, urea is subjected to a thermal decomposition reaction to obtain the carbon nitride.
[0067] In some embodiments, the preparation method of the carbon nitride is: urea is placed in a porcelain boat, then placed in a tubular furnace, and under the protection of nitrogen, the temperature is increased from room temperature to 500°C-600°C at a heating rate of 3°C / min-7°C / min, and thermally decomposed for 2h-4h, and then naturally cooled to room temperature to obtain carbon nitride powder; the flow rate of the nitrogen is 15mL / min-25mL / min.
[0068] In some embodiments, in step S1, the mass ratio of the carbon nitride to the starch is 1:(1-5); the mass volume ratio of the total mass of the carbon nitride and the starch to the anhydrous ethanol is 3g:(100mL-300mL); and / or
[0069] In the step S1, the mixing is to place the container containing carbon nitride, starch and anhydrous ethanol into an ultrasonic instrument for ultrasonic dispersion for 20 minutes to 40 minutes, and then stir with a magnetic stirrer for 5 hours to 7 hours.
[0070] In some embodiments, in step S2, the mixture obtained in step S1 is filtered to separate anhydrous ethanol and mixed powder, and the mixed powder is placed in a forced air drying oven at 50° C.-70° C. and dried for 10 h-14 h.
[0071] In some embodiments, in step S3, the dried mixed powder is placed in a porcelain boat and sent into a tube furnace. Under the protection of nitrogen, the temperature is increased to 180°C-220°C at a heating rate of 3°C / min-7°C / min and kept for 3h-5h for cross-linking pre-carbonization.
[0072] In some embodiments, in step S4, after the cross-linking pre-carbonization of step S3 is completed, the temperature is continued to be increased to 800°C-1600°C at a heating rate of 3°C / min-7°C / min for pyrolysis reaction for 1h-3h to obtain the nitrogen-doped porous hard carbon for the negative electrode of the sodium ion battery.
[0073] In an embodiment of the present invention, a nitrogen-doped porous hard carbon for a negative electrode of a sodium ion battery is prepared by the above-mentioned method for preparing a nitrogen-doped porous hard carbon for a negative electrode of a sodium ion battery.
[0074] In an embodiment of the present invention, a negative electrode for a sodium ion battery is prepared from the nitrogen-doped porous hard carbon described above.
[0075] In an embodiment of the present invention, a sodium ion battery is prepared by using the nitrogen-doped porous hard carbon as the negative electrode material.
[0076] The following describes the invention in conjunction with specific embodiments.
[0077] Example 1
[0078] A method for preparing nitrogen-doped porous hard carbon for a negative electrode of a sodium ion battery comprises the following steps:
[0079] Preparation of carbon nitride: 17 g of urea was placed in a porcelain boat and placed in a tube furnace. The temperature was raised from room temperature to 550°C at a rate of 5°C / min in an inert gas atmosphere, and pyrolyzed at 550°C for 3 hours with a nitrogen flow rate of 20 ml / min. After the reaction was completed, the temperature was naturally lowered to room temperature to obtain about 0.5 g of light yellow carbon nitride powder.
[0080] Preparation of nitrogen-doped porous hard carbon: 0.5g carbon nitride and 2.5g starch are placed in a beaker, and an appropriate amount of anhydrous ethanol is added to the beaker, and then placed in an ultrasonic instrument for ultrasonic dispersion for 30 minutes. Subsequently, the carbon nitride and starch are fully mixed by stirring with a magnetic stirrer for 6 hours. Then, the ethanol and the mixed powder are separated by a suction filtration device. The mixed powder is placed in a blast drying oven and dried at 60°C for 12 hours. The dried mixed powder is placed in a porcelain boat and sent to a tube furnace. In an inert gas (nitrogen) atmosphere, the temperature is raised from room temperature to 200°C at 5°C / min, and the mixed powder is kept at 200°C for 4 hours to cross-link and pre-carbonize; after the cross-linking and pre-carbonization is completed, the temperature is raised from 200°C to 800°C at 5°C / min, and the pyrolysis reaction is carried out at 800°C for 2 hours. After the pyrolysis reaction is completed, the temperature is naturally cooled to room temperature. The target product, nitrogen-doped porous hard carbon, is obtained. Named CNHC-800.
[0081] Example 2
[0082] A method for preparing nitrogen-doped porous hard carbon for a negative electrode of a sodium ion battery comprises the following steps:
[0083] Preparation of carbon nitride: 17 g of urea was placed in a porcelain boat and placed in a tube furnace. The temperature was raised from room temperature to 550°C at a rate of 5°C / min in an inert gas atmosphere, and pyrolyzed at 550°C for 3 hours with a nitrogen flow rate of 20 ml / min. After the reaction was completed, the temperature was naturally lowered to room temperature to obtain about 0.5 g of light yellow carbon nitride powder.
[0084] Preparation of nitrogen-doped porous hard carbon: 0.5g carbon nitride and 2.5g starch were placed in a beaker, and an appropriate amount of anhydrous ethanol was added to the beaker, and then placed in an ultrasonic instrument for ultrasonic dispersion for 30 minutes. Subsequently, the carbon nitride and starch were fully mixed by stirring with a magnetic stirrer for 6 hours. Then, the ethanol and the mixed powder were separated by a suction filtration device. The mixed powder was placed in a blast drying oven and dried at 60°C for 12 hours. The dried mixed powder was placed in a porcelain boat and sent to a tube furnace. Under an inert gas atmosphere, the temperature was raised from room temperature to 200°C at 5°C / min, and the mixed powder was kept at 200°C for 4 hours to cross-link and pre-carbonize; after the cross-linking and pre-carbonization was completed, the temperature was raised from 200°C to 1000°C at 5°C / min, and the pyrolysis reaction was carried out at 1000°C for 2 hours. After the pyrolysis reaction was completed, the temperature naturally dropped to room temperature. The target product, nitrogen-doped porous hard carbon, was obtained. Named CNHC-1000.
[0085] Example 3
[0086] A method for preparing nitrogen-doped porous hard carbon for a negative electrode of a sodium ion battery comprises the following steps:
[0087] Preparation of carbon nitride: 17 g of urea was placed in a porcelain boat and placed in a tube furnace. The temperature was raised from room temperature to 550°C at a rate of 5°C / min in an inert gas atmosphere, and pyrolyzed at 550°C for 3 hours with a nitrogen flow rate of 20 ml / min. After the reaction was completed, the temperature was naturally lowered to room temperature to obtain about 0.5 g of light yellow carbon nitride powder.
[0088] Preparation of nitrogen-doped porous hard carbon: 0.5g carbon nitride and 2.5g starch were placed in a beaker, and an appropriate amount of anhydrous ethanol was added to the beaker, and then placed in an ultrasonic instrument for ultrasonic dispersion for 30 minutes. Subsequently, the carbon nitride and starch were fully mixed by stirring with a magnetic stirrer for 6 hours. Then, the ethanol and the mixed powder were separated by a suction filtration device. The mixed powder was placed in a blast drying oven and dried at 60°C for 12 hours. The dried mixed powder was placed in a porcelain boat and sent to a tube furnace. Under an inert gas atmosphere, the temperature was raised from room temperature to 200°C at 5°C / min, and the mixed powder was kept at 200°C for 4 hours to cross-link and pre-carbonize; after the cross-linking and pre-carbonization was completed, the temperature was raised from 200°C to 1200°C at 5°C / min, and the pyrolysis reaction was carried out at 1200°C for 2 hours. After the pyrolysis reaction was completed, the temperature naturally dropped to room temperature. The target product, nitrogen-doped porous hard carbon, was obtained. Named CNHC-1200.
[0089] Example 4
[0090] A method for preparing nitrogen-doped porous hard carbon for a negative electrode of a sodium ion battery comprises the following steps:
[0091] Preparation of carbon nitride: 17 g of urea was placed in a porcelain boat and placed in a tube furnace. The temperature was raised from room temperature to 550°C at a rate of 5°C / min in an inert gas atmosphere, and pyrolyzed at 550°C for 3 hours with a nitrogen flow rate of 20 ml / min. After the reaction was completed, the temperature was naturally lowered to room temperature to obtain about 0.5 g of light yellow carbon nitride powder.
[0092] Preparation of nitrogen-doped porous hard carbon: 0.5g carbon nitride and 2.5g starch were placed in a beaker, and an appropriate amount of anhydrous ethanol was added to the beaker, and then placed in an ultrasonic instrument for ultrasonic dispersion for 30 minutes. Subsequently, the carbon nitride and starch were fully mixed by stirring with a magnetic stirrer for 6 hours. Then, the ethanol and the mixed powder were separated by a suction filtration device. The mixed powder was placed in a blast drying oven and dried at 60°C for 12 hours. The dried mixed powder was placed in a porcelain boat and sent to a tube furnace. Under an inert gas atmosphere, the temperature was raised from room temperature to 200°C at 5°C / min, and the mixed powder was kept at 200°C for 4 hours to cross-link and pre-carbonize; after the cross-linking and pre-carbonization was completed, the temperature was raised from 200°C to 1400°C at 5°C / min, and the pyrolysis reaction was carried out at 1400°C for 2 hours. After the pyrolysis reaction was completed, the temperature naturally dropped to room temperature. The target product, nitrogen-doped porous hard carbon, was obtained. Named CNHC-1400.
[0093] Example 5
[0094] A method for preparing nitrogen-doped porous hard carbon for a negative electrode of a sodium ion battery comprises the following steps:
[0095] Preparation of carbon nitride: 17 g of urea was placed in a porcelain boat and placed in a tube furnace. The temperature was raised from room temperature to 550°C at a rate of 5°C / min in an inert gas atmosphere, and pyrolyzed at 550°C for 3 hours with a nitrogen flow rate of 20 ml / min. After the reaction was completed, the temperature was naturally lowered to room temperature to obtain about 0.5 g of light yellow carbon nitride powder.
[0096] Preparation of nitrogen-doped porous hard carbon: 0.5g carbon nitride and 2.5g starch were placed in a beaker, and an appropriate amount of anhydrous ethanol was added to the beaker, and then placed in an ultrasonic instrument for ultrasonic dispersion for 30 minutes. Subsequently, the carbon nitride and starch were fully mixed by stirring with a magnetic stirrer for 6 hours. Then, the ethanol and the mixed powder were separated by a suction filtration device. The mixed powder was placed in a blast drying oven and dried at 60°C for 12 hours. The dried mixed powder was placed in a porcelain boat and sent to a tube furnace. Under an inert gas atmosphere, the temperature was raised from room temperature to 200°C at 5°C / min, and the mixed powder was kept at 200°C for 4 hours to cross-link and pre-carbonize; after the cross-linking and pre-carbonization was completed, the temperature was raised from 200°C to 1600°C at 5°C / min, and the pyrolysis reaction was carried out at 1600°C for 2 hours. After the pyrolysis reaction was completed, the temperature naturally dropped to room temperature. The target product, nitrogen-doped porous hard carbon, was obtained. Named CNHC-1600.
[0097] Example 6
[0098] A sodium ion battery is a button-type battery made by assembling the nitrogen-doped porous hard carbon for the sodium ion battery negative electrode prepared in Example 1 as the negative electrode material.
[0099] Example 7
[0100] A sodium ion battery is a button-type battery made by assembling the nitrogen-doped porous hard carbon for the sodium ion battery negative electrode prepared in Example 2 as the negative electrode material.
[0101] Example 8
[0102] A sodium ion battery is a button-type battery made by assembling the nitrogen-doped porous hard carbon for the sodium ion battery negative electrode prepared in Example 3 as the negative electrode material.
[0103] Example 9
[0104] A sodium ion battery is a button-type battery made by assembling the nitrogen-doped porous hard carbon for the sodium ion battery negative electrode prepared in Example 4 as the negative electrode material.
[0105] Among them, the physical picture of the sodium ion battery prepared in this embodiment is as follows Figure 7 shown.
[0106] Example 10
[0107] A sodium ion battery is a button-type battery made by assembling the nitrogen-doped porous hard carbon for the sodium ion battery negative electrode prepared in Example 5 as the negative electrode material.
[0108] Comparative Example 1
[0109] A method for preparing hard carbon comprises the following steps:
[0110] In an inert gas atmosphere, the starch was heated from room temperature to 200°C at a rate of 5°C / min, and kept at 200°C for 4 hours for cross-linking pre-carbonization; after the cross-linking pre-carbonization was completed, the starch was heated from 200°C to 1400°C at a rate of 5°C / min, and pyrolyzed at 1400°C for 2 hours. After the pyrolysis reaction was completed, the starch was naturally cooled to room temperature. The product, hard carbon, was obtained. It was named HC-1400.
[0111] Comparative Example 2
[0112] A sodium ion battery is a button-type battery made by assembling the hard carbon obtained in comparative example 1 as a negative electrode material.
[0113] (I) Morphological characterization by scanning electron microscopy
[0114] The nitrogen-doped porous hard carbons prepared in Examples 1 to 5 and the hard carbon prepared in Comparative Example 1 were characterized by scanning electron microscopy (SEM). Figures 1 to 6 shown.
[0115] Depend on Figure 1 It can be seen that the nitrogen-doped porous hard carbon prepared by pyrolysis reaction at 800° C. in Example 1 has a pore structure.
[0116] Depend on Figures 2 to 5 It can be seen that the nitrogen-doped porous hard carbons obtained by pyrolysis reactions at 1000°C, 1200°C, 1400°C, and 1600°C in Examples 2 to 5, respectively, all have rich pore structures.
[0117] Depend on Figure 6 It can be seen that the hard carbon prepared by pyrolysis reaction at 1400° C. in Comparative Example 1 has a lamellar microstructure and does not have a pore structure because the hard carbon is not doped with nitrogen.
[0118] (II) XPS diffraction nitrogen element detection
[0119] The nitrogen-doped porous hard carbon prepared in Example 1 was detected by X-ray photoelectron spectroscopy (XPS). Figure 7 As shown. Figure 7 It can be seen that in the prepared nitrogen-doped porous hard carbon, nitrogen is successfully doped into the hard carbon, and the nitrogen atoms exist in the nitrogen-doped porous hard carbon in the form of "graphitic nitrogen". Graphitic nitrogen is a type of nitrogen atom existing in carbon materials. One graphitic nitrogen atom is bonded to three carbon atoms and contains lone pairs of electrons, which can improve the charge transfer efficiency of hard carbon.
[0120] (III) Morphological characterization of button cells
[0121] For a physical picture of the sodium ion battery prepared in Example 9, please see Figure 8 .Depend on Figure 8It can be seen that the button battery prepared by the present invention, which uses nitrogen-doped porous hard carbon prepared by the co-pyrolysis reaction of carbon nitride and starch as the negative electrode material, does not experience expansion and foaming, thus solving the problem of expansion, melting and foaming caused by pyrolysis of pure starch.
[0122] Among them, starch begins to dehydrate, decompose and carbonize at 300°C, and is completely carbonized at about 600°C. The decomposition temperature of carbon nitride is above 600°C. Therefore, before the starch particles are completely carbonized at 600°C, they are isolated by carbon nitride and will not melt and foam.
[0123] (IV) Constant current charge and discharge test
[0124] The sodium ion batteries prepared in Examples 6 to 10 and Comparative Example 2 were subjected to constant current charge and discharge tests at a current density of 30 mA / g. The test results are shown in Figures 9 to 14 .
[0125] Depend on Fig. 9 It can be seen that the first discharge specific capacity of the sodium ion battery prepared in Example 6 reached 404.5 mAh / g, the discharge specific capacity was 207 mAh / g, and the first cycle coulombic efficiency was 51.17%.
[0126] Depend on Fig.10 It can be seen that the first discharge specific capacity of the sodium ion battery prepared in Example 7 reached 398.2 mAh / g, the discharge specific capacity was 245.3 mAh / g, and the first cycle coulombic efficiency was 61.59%.
[0127] Depend on Fig.11 It can be seen that the first discharge specific capacity of the sodium ion battery prepared in Example 8 reached 430.9 mAh / g, the discharge specific capacity was 277.1 mAh / g, and the first cycle coulombic efficiency was 64.31%.
[0128] Depend on Fig.12 It can be seen that the first discharge specific capacity of the sodium ion battery prepared in Example 9 reached 443.5 mAh / g, the discharge specific capacity was 295.4 mAh / g, and the first cycle coulombic efficiency was 66.61%.
[0129] Depend on Fig.13 It can be seen that the first discharge specific capacity of the sodium ion battery prepared in Example 10 reached 394.2 mAh / g, the discharge specific capacity was 269 mAh / g, and the first cycle coulombic efficiency was 68.24%.
[0130] Depend on Fig.14 It can be seen that the first discharge specific capacity of the sodium ion battery prepared in Comparative Example 2 is only 249.9 mAh / g, the discharge specific capacity is only 64.6 mAh / g, and the first-cycle coulombic efficiency is only 25.86%.
[0131] It can be seen that the sodium ion battery prepared in Comparative Example 2 has a small first discharge specific capacity, a small discharge specific capacity, and a very low first cycle coulombic efficiency. The sodium ion battery prepared in the present invention has the advantages of a large first discharge specific capacity, a large discharge specific capacity, and a high first cycle coulombic efficiency.
[0132] (V) Constant current charge and discharge test
[0133] The sodium ion batteries prepared in Examples 6 to 10 and Comparative Example 2 were subjected to 300-cycle performance tests at a current density of 1000 mAh / g. The test results are shown in Figures 15 to 20 .
[0134] Depend on Fig.15 It can be seen that the sodium ion battery prepared in Example 6 has an initial discharge capacity of 168.4 mAh / g at a current density of 1000 mAh / g. After 300 charge and discharge cycles, the discharge capacity is 126.9 mAh / g, the capacity retention rate is 75.3%, and the cycle stability is good.
[0135] Depend on Fig.16 It can be seen that the sodium ion battery prepared in Example 7 has an initial discharge capacity of 205.8 mAh / g at a current density of 1000 mAh / g. After 300 charge and discharge cycles, the discharge capacity is 154.5 mAh / g, the capacity retention rate is 75.0%, and the cycle stability is good.
[0136] Depend on Fig.17 It can be seen that the sodium ion battery prepared in Example 8 has an initial discharge capacity of 236.3 mAh / g at a current density of 1000 mAh / g. After 300 charge and discharge cycles, the discharge capacity is 196.9 mAh / g, the capacity retention rate is 83.3%, and the cycle stability is good.
[0137] Depend on Fig.18 It can be seen that the sodium ion battery prepared in Example 9 has an initial discharge capacity of 293.4 mAh / g at a current density of 1000 mAh / g. After 300 charge and discharge cycles, the discharge capacity is 222.8 mAh / g, the capacity retention rate is 75.9%, and the cycle stability is good.
[0138] Depend on Fig.19 It can be seen that the sodium ion battery prepared in Example 10 has an initial discharge capacity of 190.9 mAh / g at a current density of 1000 mAh / g. After 300 charge and discharge cycles, the discharge capacity is 159.3 mAh / g, the capacity retention rate is 83.4%, and the cycle stability is good.
[0139] Depend on Fig. 20It can be seen that the sodium ion battery prepared in Comparative Example 2 has an initial discharge capacity of only 35.5 mAh / g at a current density of 1000 mAh / g. After 300 charge and discharge cycles, the discharge capacity is only 11.2 mAh / g.
[0140] It can be seen that the specific capacity of the sodium ion battery prepared in Comparative Example 2 is very low and has almost no sodium storage performance. The sodium ion battery prepared in the present invention has a large specific capacity and excellent sodium storage performance.
[0141] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A method for preparing nitrogen-doped porous hard carbon for a negative electrode of a sodium ion battery, characterized in that: The following steps are involved: S1. Mixing carbon nitride and starch: placing carbon nitride, starch and anhydrous ethanol in a container and then mixing them to obtain a mixture; S2, solid-liquid separation and drying: separating the mixture obtained in step S1 into anhydrous ethanol and mixed powder, and drying the mixed powder; S3, cross-linking pre-carbonization: under the protection of inert gas, heating the mixed powder dried in step S2 for cross-linking pre-carbonization; S4, pyrolysis reaction: After the cross-linking pre-carbonization of step S3 is completed, the temperature is continued to be raised to carry out pyrolysis reaction, so as to obtain the nitrogen-doped porous hard carbon for the negative electrode of the sodium ion battery.
2. The method for preparing a nitrogen-doped porous hard carbon for a negative electrode of a sodium ion battery according to claim 1, characterized in that: In the step S1, the method for preparing the carbon nitride is: under the protection of an inert gas, urea is subjected to a thermal decomposition reaction to obtain the carbon nitride.
3. The method for preparing a nitrogen-doped porous hard carbon for a negative electrode of a sodium ion battery according to claim 2, characterized in that: The preparation method of the carbon nitride is as follows: urea is placed in a porcelain boat, then placed in a tubular furnace, and heated from room temperature to 500°C-600°C at a heating rate of 3°C / min-7°C / min under the protection of nitrogen for thermal decomposition for 2h-4h, and then naturally cooled to room temperature to obtain carbon nitride powder; the flow rate of the nitrogen is 15mL / min-25mL / min.
4. The method for preparing nitrogen-doped porous hard carbon for a negative electrode of a sodium ion battery according to claim 1, characterized in that: In step S1, the mass ratio of the carbon nitride to the starch is 1:(1-5); the mass volume ratio of the total mass of the carbon nitride and the starch to the absolute ethanol is 3g:(100mL-300mL); and / or In the step S1, the mixing is to place the container containing carbon nitride, starch and anhydrous ethanol into an ultrasonic instrument for ultrasonic dispersion for 20 min-40 min, and then stir with a magnetic stirrer for 5 h-7 h.
5. The method for preparing nitrogen-doped porous hard carbon for a negative electrode of a sodium ion battery according to claim 1, characterized in that: In the step S2, the mixture obtained in the step S1 is filtered to separate the anhydrous ethanol and the mixed powder, and the mixed powder is placed in a forced air drying oven at 50° C.-70° C. and dried for 10 h-14 h.
6. The method for preparing nitrogen-doped porous hard carbon for a negative electrode of a sodium ion battery according to claim 1, characterized in that: In step S3, the dried mixed powder is placed in a porcelain boat and sent into a tube furnace. Under the protection of nitrogen, the temperature is increased to 180°C-220°C at a heating rate of 3°C / min-7°C / min and kept for 3h-5h for cross-linking pre-carbonization.
7. The method for preparing nitrogen-doped porous hard carbon for a negative electrode of a sodium ion battery according to claim 1, characterized in that: In the step S4, after the cross-linking pre-carbonization of step S3 is completed, the temperature is continued to be raised to 800°C-1600°C at a heating rate of 3°C / min-7°C / min for pyrolysis reaction for 1h-3h to obtain the nitrogen-doped porous hard carbon for the negative electrode of the sodium ion battery.
8. A nitrogen-doped porous hard carbon for a negative electrode of a sodium ion battery, characterized in that: It is prepared by the preparation method of nitrogen-doped porous hard carbon for sodium ion battery negative electrode according to any one of claims 1 to 7.
9. A sodium ion battery negative electrode, characterized in that: It is made from the nitrogen-doped porous hard carbon according to any one of claims 1 to 8.
10. A sodium ion battery, characterized in that: The nitrogen-doped porous hard carbon according to any one of claims 1 to 8 is used as the negative electrode material.
Citation Information
Patent Citations
Starch-based sodium ion battery negative electrode material and preparation method thereof
CN118439585A
Hard carbon microsphere negative electrode material and preparation method and application thereof
CN118538913A
Carbon-coated nitrogen-rich g-C3N4, negative electrode material and preparation method thereof
CN110148713A
Biomass hard carbon negative electrode material of sodium ion battery and preparation method of biomass hard carbon negative electrode material
CN113206246A
Hard carbon material as well as preparation method and application thereof
CN113800496A